Correlation between Delayed Diagnosis and Stage at Presentation in Gynecological Cancers among Women in Low-Resource Settings. A Cross-Sectional Study - Nosheen Sikandar Baloch, Hanana Hameed, Lubna Aslam, Syeda Shaista Waheed, Rizwana Nawaz, Nomira Waheed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Gynecological cancers remain a major health burden among women in low-resource settings, where late-stage presentation is common due to diagnostic delays. Timely detection plays a critical role in improving survival outcomes. Objectives: This study aimed to investigate the correlation between delayed diagnosis and stage at presentation in gynecological cancers among women from two major public hospitals in Pakistan. Methodology: A cross-sectional study was conducted over ten months (December 2022 to March 2023) involving 48 women with histologically confirmed gynecological cancers at Lahore General Hospital, Lahore, and Bolan Medical Complex Hospital, Quetta. Data on demographics, presenting symptoms, first healthcare contact, referral pattern, and diagnostic timelines were collected using a structured proforma. Diagnostic delay was defined as the interval from first symptom onset to histopathological confirmation, and cancer stage was classified using FIGO criteria. Data were analyzed using SPSS version 25.0, and associations were evaluated using chi-square and Fisher’s exact tests with p < 0.05 considered significant. Results: Of the 48 patients, 56.2% experienced diagnostic delays greater than three months. A significant association was observed between prolonged delay and late-stage presentation (p = 0.001). Patients from rural areas, low socioeconomic backgrounds, and those who first consulted non-specialist providers or traditional healers were more likely to face delays. Furthermore, patients from Bolan Medical Complex had a higher proportion of delayed diagnoses (88.9%) compared to Lahore General Hospital (56.4%), with a statistically significant difference (p = 0.04). Conclusion: Delayed diagnosis significantly correlates with advanced-stage gynecological cancer. Strengthening referral systems, public awareness, and early detection infrastructure is essential to reduce diagnostic delays in low-resource settings. Keywords: Gynecological Cancers, Diagnostic delay, Stage at presentation, Low-resource settings, Healthcare Access.